The Effect of Weight Exercise on The Legs Toward Shooting Ability in Tanjung Enim Football School Students - Yudi Sapura; Renanto Renanto (Universitas PGRI Palembang, 2023)
This study aims to determine whether there is an influence between weight training on the legs on the results of shooting football at Tanjung Enim football school students. The method used was an experiment with the one group pre test post test design, namely statistics to determine the effect between two symptoms. The data collection technique used was test. Goal shooting test to measure the result of shooting s in football game. The samples was 18 students. The result obtained, there is a strong correlation between weight training on the legs on the results of shooting s in Tanjung Enim football school students, the magnitude of the influence between weight training on the legs on the results of shooting s can be seen with the hypothesis using the t test to obtain a tcount of 1.11 and a ttable value of 1.04. So tcount > ttable, thus Ha is accepted and Ho is rejected, which means that there is a significant effect of weight training on the legs on the results of shooting football in Tanjung Enim football school students.